Exploring the role of soundscape in restorative experience: A pilot study from children’s perspective - Shu, Shan (Frontiers in Psychology, 2023)
Indoor and outdoor noise is renowned for its ability to negatively affect children’s health and performance. However, the possible restorative benefits of everyday soundscapes in children are still poorly understood. This study aimed to explore the role of everyday soundscapes in children’s restorative experiences in frequented indoor (classroom) and outdoor (urban park) environments. In stage one, 335 children (7-12 years old) were interviewed using a questionnaire survey to investigate their restoration needs, restorative experience, and potential restorative sounds. In stage two, 61 children participated in a laboratory study to assess the perceived restorativeness of different soundscapes, which were combinations of potential restorative sounds and background noise, under signal-to-noise ratios (SNRs) from -5 to 15 dB. The findings denoted that the children’s need for restoration increased with age significantly. Younger children reported that the role of the sound environment was more important in their classroom experiences than in urban parks. Although the types of music displayed in surveyed parks were generally not preferred by the children, music was assessed as the most restorative sound in the laboratory study. Additionally, natural sounds were perceived to be more restorative than background noise in the context. In particular, birdsong showed more restorativeness in the classroom context, whereas fountain sounds showed more restorativeness in the park context. Additionally, an SNR of at least 5 dB is desirable when considering the restorative experiences of children in classrooms and urban parks.